2023
DOI: 10.1002/btpr.3336
|View full text |Cite
|
Sign up to set email alerts
|

Use of scanning electron microscopy and energy dispersive X‐ray spectroscopy to identify key fouling species during alternating tangential filtration

Abstract: Alternating tangential flow filtration (ATF) has become one of the primary methods for cell retention and clarification in perfusion bioreactors. However, membrane fouling can cause product sieving losses that limit the performance of these systems. This study used scanning electron microscopy and energy dispersive X‐ray spectroscopy to identify the nature and location of foulants on 0.2 μm polyethersulfone hollow fiber membranes after use in industrial Chinese hamster ovary cell perfusion bioreactors for mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…Antifoam micelle was detected on fouled hollow fiber membrane surface by Kelly et al (Kelly et al, 2014), but we did not find silicon, a major element of antifoam, enriched in foulant patches. Silicon was also not observed by Sundar et al (Sundar et al, 2023). It's worth noting that Kelly et al (Kelly et al, 2014) imaged the frozen membrane without washing, but Sundar et al (Sundar et al, 2023) and we washed the membrane before imaging.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Antifoam micelle was detected on fouled hollow fiber membrane surface by Kelly et al (Kelly et al, 2014), but we did not find silicon, a major element of antifoam, enriched in foulant patches. Silicon was also not observed by Sundar et al (Sundar et al, 2023). It's worth noting that Kelly et al (Kelly et al, 2014) imaged the frozen membrane without washing, but Sundar et al (Sundar et al, 2023) and we washed the membrane before imaging.…”
Section: Discussionmentioning
confidence: 67%
“…Silicon was also not observed by Sundar et al (Sundar et al, 2023). It's worth noting that Kelly et al (Kelly et al, 2014) imaged the frozen membrane without washing, but Sundar et al (Sundar et al, 2023) and we washed the membrane before imaging.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, this study does not allow us to distinguish between the beneficial contributions of backflushing at both the inlet and outlet, utilization of the entire membrane surface, and/or relaxation of the fouling deposit when the crossflow direction changes. The rTFF_2 run with higher amount of cell culture debris showed lower product sieving than rTFF_1 (Figure 5d), highlighting that rTFF is still prone to product retention which can likely be attributed to pronounced fouling at the inlet or exit of the hollow fiber modules at elevated debris levels (Sundar et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This causes an increase in the drag forces that push particles into the membrane (Ripperger & Altmann, 2002), which can lead to a denser deposit and greater particle penetration into the membrane, both detectable as an increase of irreversible fouling resistance (Weinberger & Kulozik, 2022). Sundar et al (2023) demonstrated that the greatest fouling in ATF systems occurs at the ends of the hollow fiber module, that is, where the filtrate flux is greatest. This might explain studies observing significant product sieving losses despite using properly sized ATF modules (Kim et al, 2016; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%